2022
DOI: 10.3390/microorganisms10061231
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia/Shigella, SCFAs, and Metabolic Pathways—The Triad That Orchestrates Intestinal Dysbiosis in Patients with Decompensated Alcoholic Cirrhosis from Western Mexico

Abstract: Gut microbiota undergoes profound alterations in alcohol cirrhosis. Microbiota-derived products, e.g., short chain fatty acids (SCFA), regulate the homeostasis of the gut-liver axis. The objective was to evaluate the composition and functions of the intestinal microbiota in patients with alcohol-decompensated cirrhosis. Fecal samples of 18 patients and 18 healthy controls (HC) were obtained. Microbial composition was characterized by 16S rRNA amplicon sequencing, SCFA quantification was performed by gas chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 84 publications
2
26
0
Order By: Relevance
“…Previous studies have shown that the abundance of Bacteroidetes and Fusobacteria increased with malignant colorectal cancer ( 22 ). Tonatiuh et al found that the gut microbiota in patients with alcoholic cirrhosis showed a significant increase in the pathogenic/pathogenic genera Escherichia/Shigella and Prevotella , and a decrease in beneficial bacteria such as Blauella , Faecalibacterium and alpha diversity decreased ( 23 ). The correlation of alcohol consumption with the abundance of Fusobacterium OTUs in cancer tissue suggested a possible link between alcohol metabolism and subsequent tumorigenesis caused by Fusobacterium ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the abundance of Bacteroidetes and Fusobacteria increased with malignant colorectal cancer ( 22 ). Tonatiuh et al found that the gut microbiota in patients with alcoholic cirrhosis showed a significant increase in the pathogenic/pathogenic genera Escherichia/Shigella and Prevotella , and a decrease in beneficial bacteria such as Blauella , Faecalibacterium and alpha diversity decreased ( 23 ). The correlation of alcohol consumption with the abundance of Fusobacterium OTUs in cancer tissue suggested a possible link between alcohol metabolism and subsequent tumorigenesis caused by Fusobacterium ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxins derived from the family Enterobacteriaceae seemed to be a key trigger for systemic inflammation. 25 Specific gut microbiota can drive neuroinflammation and even influence brain function and behavior in rodents and humans. 26 Increased Enterobacteriaceae, a peculiar gut microbiota composition of Parkinsonian patients, has been implicated in disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe CRF changes in the stool microbial composition were characterized by a lower abundance of gut microbiota capable of SCFA production and have a relative overgrowth of potentially pathogenic taxa. Endotoxins derived from the family Enterobacteriaceae seemed to be a key trigger for systemic inflammation 25 . Specific gut microbiota can drive neuroinflammation and even influence brain function and behavior in rodents and humans 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The content of SCFAs in the colon contents was determined by gas chromatography as previously described and optimized [ 35 ]. The stool sample (about 0.15 g) was weighed, and 1000 μL and 50 μL of 50% sulfuric acid were added and then centrifuged at 5000× g for 10 min.…”
Section: Methodsmentioning
confidence: 99%